2016
DOI: 10.5858/arpa.2015-0176-rs
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Colitis: An Uncommon Mimicker of Common Colitides

Abstract: Cytomegalovirus latency, though ubiquitous in the human population, is known to cause colitis in both immunocompromised and immunocompetent hosts. Furthermore, the clinical, endoscopic, and histologic appearance of cytomegalovirus colitis can mimic that of inflammatory bowel disease, an extremely well-documented disease. In this context, though many reports have looked at inflammatory bowel disease with superimposed cytomegalovirus infection, less attention has been paid to cytomegalovirus as a primary cause o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Although this patient’s initial presentation did not involve GI tract symptoms, during her admission she subsequently developed symptoms and was found to have tissue-invasive disease. CMV infection is commonly considered as a part of the differential diagnosis in patients presenting with IBD flare symptoms given its predilection for the colon 20. Involvement of the oesophagus and duodenum, however, may be more unusual in this population, although CMV oesophagitis is not uncommon in patients with additional immunosuppression or immunodeficiency 21 22.…”
Section: Discussionmentioning
confidence: 99%
“…Although this patient’s initial presentation did not involve GI tract symptoms, during her admission she subsequently developed symptoms and was found to have tissue-invasive disease. CMV infection is commonly considered as a part of the differential diagnosis in patients presenting with IBD flare symptoms given its predilection for the colon 20. Involvement of the oesophagus and duodenum, however, may be more unusual in this population, although CMV oesophagitis is not uncommon in patients with additional immunosuppression or immunodeficiency 21 22.…”
Section: Discussionmentioning
confidence: 99%
“…In CMV retinitis patients administered with induction therapy with foscarnet, ocular symptoms were initially relieved but recurred soon after stopping the treatment (Heiden et al, 2019). Cidofovir competitively inhibits DNA elongation (Britt and Prichard, 2018) and is helpful for treating colitis (Baniak and Kanthan, 2016). Cottone et al (2001) showed that antiviral treatment can relieve the clinical symptoms of patients (among five patients, three with ganciclovir and two with foscarnet) with ulcerative colitis.…”
Section: Potential Therapeutic Targetsmentioning
confidence: 99%
“…While a high CMV viral load in the setting of diarrhea and colitis is suggestive of CMV colitis, histopathology remains the gold standard for diagnosing enteric CMV disease [26,51]. On direct visual examination, CMV disease often appears as occasional erosions, ulcerations, or even mucosal hemorrhages.…”
Section: Colonoscopymentioning
confidence: 99%
“…On direct visual examination, CMV disease often appears as occasional erosions, ulcerations, or even mucosal hemorrhages. Less frequently it can cause confluent ulcerations, similar in appearance to inflammatory bowel disease, or even pseudomembranes [51]. Histopathologic features of enteric CMV disease are typically characterized by enlarged cells containing intranuclear inclusion bodies (known as "Cowdry bodies") surrounded by a halo [51].…”
Section: Colonoscopymentioning
confidence: 99%
See 1 more Smart Citation